Początki kształtowania literackiej legendy Jakuba Jasińskiego w twórczości Adama Mickiewicza = The beginnings of Jakub Jasiński's literary legend formation in selected works by Adam Mickiewicz - Tomicka, Aleksandra (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Adam Mickiewicz immortalized Jakub Jasinski's image in Polish people mind through introducing him to some of his literary works. Sketch discusses the general?s effigy in "Sir Thaddeus" ["Pan Tadeusz"] and unfinished drama "Jakub Jasinski, two Poland" ["Jakub Jasiński, czyli dwie Polski"]. The beginning of the nineteenth century was the time of looking for outstanding patriotic national heroes, famous for courage and sacrifice for the homeland. Jasinski worked secretly as a soldier, through which he managed to organize a conspiracy in Vilnius in 1794. His political and social program, based on revolutionary France, earned him many enemies. The conflict between him and Kosciuszko probably had personal background. Jasinski's last decision to take the fight with an army of Suvorov and his death on the ramparts of Warsaw Prague contributed to consolidate its image in the memory of future generations as a national leader, the soldier inspired to heroic battle, the defender of the homeland obsessed with patriotic elation. The purpose of this article is an attempt to show the shaping of Jakub Jasinski?s literary legend, whose forming is contributed to Mickiewicz.
Keywords: Mickiewicz, Adam (1798-1855); Jasiński, Jakub (generał; 1761-1794); Powstanie 1794 r. Kościuszkowskie; patriotyzm; Insurrection; patriotism